Sharia Solutions to Minimising Personal Bankruptcy Cases in Malaysia: A Juristic Analysis - Abdullah, Md. Faruk; Hoque, Muhammad Nazmul; Rahman, Md. Habibur; Said, Jamaliah (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This study aims to analyze sharia principles in the practice of loans and debts to minimize bankruptcy cases among the public. Some elements in sharia may have an impact on changing the behavior and attitude of debtors. First, sharia prohibits individuals from taking loans for luxury goods although this is permissible in sharia. Second, people are urged to be careful in spending their money and be careful not to give in to lust. Lastly, there is genuine concern within sharia for the repayment of loans and debts. In addition, sharia also advises creditors to extend the repayment period without charging interest if the debtor is in trouble. For Islamic financial institutions, Sharia regulates profit and loss sharing contracts. Furthermore, various types of charity, for example zakat, alms, and waqf, can be used in Muslim societies to protect debtors from bankruptcy. This study adds new knowledge in Islamic financial literacy, which will contribute to improving people's financial well-being.